DEMOGRAPHIC BONUS ANALYSIS AND ECONOMIC GROWTH OF EAST JAVA - Amirusholihin; Listiono (East Java Economic Journal, 2018)
BKKBN predicts that Indonesia will get demographic bonus in 2020 until 2030. The question is whether the demographic bonus has a positive impact on the economy of East Java or even a negative impact. Based on data from BPS, by 2015 the workingage population in East Java is around 69.4 percent of the total population, while the child and old-age is 30.6 percent. The size of the working-age population is closely related to the amount of labor, which also greatly determines the amount of output on goods and services produced. This paper aims to explain how the impact of demographic bonuses on East Java's regional economy, based on the Solow model extended to include demographic variables. The analysis uses a dynamic panel model by 38 districts in East Java that have demographic bonuses in 2020 with GDP as a reference in determining the growth of economists. From these analyzes it can be seen the impact of demographic bonuses in East Java as an advantage or even create new spatial inequality between regions.